Second-dose measles vaccination and associated factors among under-five children in urban areas of North Shoa Zone, Central Ethiopia, 2022 - Tadesse, Addisu Waleligne; Sahlu, Degemu; Benayew, Mengistu (Frontiers in Public Health, 2022)
Introduction: Measles remains a leading cause of vaccine-preventable infant mortality. In Africa, about 13 million cases and 650,000 deaths occur annually, with sub-Saharan Africa having the highest morbidity and mortality. Ethiopia launched MCV2 into the routine immunization program in 2019. However, little has been known about the coverage of the second dose measles vaccine. Therefore, the purpose of this study was to assess the level of second-dose measles vaccine uptake and associated factors in North Shoa Zone, Central Ethiopia. Method: Community-based cross-sectional study was conducted with sample size of 410. . The study units were selected consecutively. The data was collected using structured interviewer-administered questionnaires. Data were coded manually and entered into Epi-data Version 4.4.2.1. Frequency and cross-tabs were used for data cleaning. Data were analyzed using SPSS Version 21 software. Multicollinearity and Model goodness-of-fit tests were checked. A multivariable logistic regression model at 95% CI was used to identify factors associated with the dependent variable. Result: The response rate was 90.7%. The level of MCV2 vaccination among children in urban areas of North Shoa Zone was 42.5% [95% CI :( 36.8, 47.3)]. Maternal age of ≤25years [AOR=9.12: 95%CI (1.97, 42.19)], 26-30 years [AOR=9.49: 95%CI (2.33, 38.63)], 31-35 years [AOR=7.87: 95%CI (1.78, 34.79)]; average time mothers had been waiting for vaccination at the health facility[AOR=3.68: 95%CI (1.33, 10.23)]; awareness about vaccine-preventable diseases[AOR=4.15: 95%CI (1.53, 11.26), and awareness on recommended measles doses [AOR=17.81: 95%CI (3.91, 81.22)] were identified as factors associated with MCV2 vaccination. The primary reason (48.1%) reported by mothers for not vaccinating MCV2 was being unaware of the need to return for MCV2 vaccination. Conclusion and Recommendation: The level of MCV2 vaccination among children in urban areas of the North Shoa Zone was low. Maternal age, average time mothers had been waiting for vaccination at the health facility, awareness about vaccine-preventable diseases, recommended age for the last immunization, and recommended measles doses were identified as factors associated with MCV2 uptake. The primary reason for not vaccinating MCV2 was a lack of information. Hence, enhancing awareness about vaccine-preventable diseases, and creating an alerting mechanism for MCV2 appointment is recommended.